Notices of Impressions of Ancient Seals, principally of the Eglinton Family (Proceedings of the Society of Antiquaries of Scotland, 1856)
A notice of a communication entitled 'Notices of impressions of ancient seals, principally of the Eglinton family' was read. Meeting notes from 11 April 1855.